Regression Analysis of Dimensions Event Volunteer Motivation Towards Intention to Volunteer - Mohd Rashid, Norhidayah; Ramli, Nurakmal; Ghazali, Ayu Rohaidah; Nordin, Azzura; Zamzuri, Norol Hamiza; Saridan, Shazril (Information Management and Business Review, 2024)
Volunteerism at events, from small to large-scale festivals such as sporting competitions, is critical to their success. Understanding event volunteers’ motivations is crucial for organizers in terms of recruiting, retaining, and managing volunteer resources efficiently. This study aims to examine the relationship between dimensions of event volunteer motivation which include leisure motivation, purposive motivation, egoistic motivation and external influence on the intention to volunteer. Previous studies have found that these multi-dimensional motivational factors are essential for fostering an individual’s decision-making process towards volunteering at an event. Positive effects on volunteer motivation will be analyzed using regression analysis in this research. In general, the results derived from the study will assist event organizers in understanding how their volunteers make decisions about taking part in the festivals they organize as well as designing ways of recruiting, managing and holding onto them for attaining ultimate success during such occasions.